Mengonsumsi Bangkai Binatang dalam Perspektif Islam dan Kesehatan - Maulidiah Vita Fadlina; Nabila Talitha Sari; Talitha Verda Aisyah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The consumption of carrion is a sensitive topic regulated in various religious traditions, including Islam, Christianity, and Judaism. Generally, Islam prohibits the consumption of carrion, except in situations where there are significant concerns regarding survival. This religious perspective aims to enforce strict adherence to maintain the sanctity and health of society. The health perspective highlights carrion as a dangerous food source because it has the potential to be contaminated with bacteria, parasites, or toxins, posing risks of diseases such as bacterial infections, food poisoning, and parasitosis. As a result, both the religious perspective and the health viewpoint agree on the warnings regarding the dangers of carrion, except in emergency situations with high ethical considerations or surgical interventions in severe cases. The purpose of this article is to explore the reasons behind the individual prohibition of consuming carrion from both religious and health perspectives and its effects on public health.